Correlations between the phenolic compounds and antioxidant activity in the skin and pulp of table grape varieties - De Souza, Angela Vacaro [UNESP]; Da Silva Vieira, Marcos Ribeiro; Putti, Fernando Ferrari [UNESP] (FapUNIFESP (SciELO), 2018)
Grapes are considered a major source of phenolic compounds when compared to other vegetables, but the great diversity amongst the cultivars results in fruits with different characteristics of taste and colour, which is certainly associated with the polyphenol content and profile. Skins and pulps of ripe samples of Itália, Brasil, Rubi, Thompson and Niagara Rosada grapes from the Campinas and Jundiaí regions - SP state - Brazil, were studied with the objective of evaluating the antioxidant activity, enzymatic activities of peroxidase and polyphenoloxidase, phenolic compounds and ascorbic acid. In order to verify correlations between the skins and pulps of the varieties and the characteristics studied, Pearson's correlation, the generalized distance of Mahalanobis (D2) and finally the grouping of the different responses using the multivariate analysis, were carried out. It was verified that the skins of the grapes analysed had a positive correlation with the phenolic compounds, polyphenoloxidase activity and ascorbic acid content, except for Niagara Rosada, showing higher levels for these evaluations. There was no correlation between the antioxidant activity and the other analyzes. This shows that for the majority of the varieties evaluated, the skins are a great source of these compounds.
Correlações entre compostos fenólicos e atividade antioxidante em casca e polpa de variedades de uva de mesa
Keywords: Antioxidant activity index; Ascorbic acid; Vitis sp.